Spectrophotometric Determination of Ezetimibe and Cefepime - GOWRI SANKAR, D.; DURVASA RAO, B.; MADHAVI LATHA, P.V.; VAMSI KRISHNA, M. (Asian Journal of Chemistry, 2010)
A simple, sensitive spectrophotometric methods has been developed for the estimation of ezetimibe and cefepime in pure as well as in pharmaceutical formulations. This method is based on the formation of diazo coupling product with N-1-napthyl-ethylene diamine dihydrochloride in the presence nitrous acid, which exhibits maximum absorbance at 555 and 570 nm for ezetimibe and cefepime, respectively. Beer’s law is obeyed at the concentration range of 2.5-12.5 μg/mL for ezetimibe and 25-125 μg/mL for cefepime, respectively.